Studying the Endothelial Glycocalyx in vitro: What Is Missing? - Haymet, Andrew B.; Bartnikowski, Nicole; Wood, Emily S.; Vallely, Michael P.; McBride, Angela; Yacoub, Sophie; Biering, Scott B.; Harris, Eva; Suen, Jacky Y.; Fraser, John F. (Frontiers in Cardiovascular Medicine, 2021)
All human cells are coated by a surface layer of proteoglycans, glycosaminoglycans (GAGs) and plasma proteins, called the glycocalyx. The glycocalyx transmits shear stress to the cytoskeleton of endothelial cells, maintains a selective permeability barrier, and modulates adhesion of blood leukocytes and platelets. Major components of the glycocalyx, including syndecans, heparan sulfate, and hyaluronan, are shed from the endothelial surface layer during conditions including ischaemia and hypoxia, sepsis, atherosclerosis, diabetes, renal disease, and some viral infections. Studying mechanisms of glycocalyx damage in vivo can be challenging due to the complexity of immuno-inflammatory responses which are inextricably involved. Previously, both static as well as perfused in vitro models have studied the glycocalyx, and have reported either imaging data, assessment of barrier function, or interactions of blood components with the endothelial monolayer. To date, no model has simultaneously incorporated all these features at once, however such a model would arguably enhance the study of vasculopathic processes. This review compiles a series of current in vitro models described in the literature that have targeted the glycocalyx layer, their limitations, and potential opportunities for further developments in this field.